Alarmingly Finding the Growth of Animal Cell (Mouse Fibroblast) in the Presence of Antinutrient Gossypol in Culture - Ismartoyo (Innovations in Biological Science Vol. 5, 2024)
An experiment was conducted to investigate the effects of gossypol on growth of animal cells in culture. A cells culture was established according to the methods of Freshney (2010). Four treatments examined were To= cells + media, Te= cells + ethanol, Tgl= cells + 5 \(μ\)M gossypol, and TgH= cells + 20 \(μ\)M gossypol. The results of this experiment indicated that the presence of gossypol 5 \(μ\)M inhibited (p<0.01) cells growth, and gossypol at 20 \(μ\)M completely stopped the increased in the numbers of cells. It was concluded that the division and growth of animal cells in culture were adversely depressed by gossypol probably due to gossypol-protein complexes which enveloping cells, preventing protein transferred from media to cells, and reduced the nutrient availability for growth.